Influence of Tryptophan Contained in 1-Methyl-Tryptophan on Antimicrobial and Immunoregulatory Functions of Indoleamine 2,3-Dioxygenase - Schmidt, Silvia K.; Siepmann, Stephan; Kuhlmann, Katja; Meyer, Helmut E.; Metzger, Sabine; Pudelko, Sabine; Leineweber, Margret; Däubener, Walter (PLOS ONE, 2012)
Indoleamine 2,3-dioxygenase (IDO) has been identified as an important antimicrobial and immunoregulatory effector molecule essential for the establishment of tolerance by regulating local tryptophan (Trp) concentrations. On the other hand, the immunosuppressive capacity of IDO can have detrimental effects for the host as it can lead to deleterious alterations of the immune response by promoting tolerance to some types of tumors. To suppress this disadvantageous IDO effect, the competitive inhibitor 1-Methyl-Tryptophan (1-MT) is being tested in clinical trials. However, it remains inconclusive which stereoisomer of 1-MT is the more effective inhibitor of IDO-mediated immunosuppression. While IDO enzyme activity is more efficiently inhibited by 1-L-MT in cell-free or in vitro settings, 1-D-MT is superior to 1-L-MT in the enhancement of anti-tumor responses in vivo. Here, we present new data showing that commercially available 1-L-MT lots contain tryptophan in amounts sufficient to compensate for the IDO-mediated tryptophan depletion in vitro. The addition of 1-L-MT abrogated IDO-mediated antimicrobial effects and permitted the growth of the tryptophan-auxotroph microorganisms Staphylococcus aureus and Toxoplasma gondii. Consistent with this, the tryptophan within 1-L-MT lots was sufficient to antagonize IDO-mediated inhibition of T cell responses. Mass spectrometry (MS) analysis revealed not only tryptophan within 1-L-MT, but also the incorporation of this tryptophan in bacterial and human proteins that were generated in the presence of 1-L-MT in otherwise tryptophan-free conditions. In summary, these data reveal that tryptophan within 1-L-MT can affect the results of in vitro studies in an L-stereospecific and IDO-independent way.